2023
DOI: 10.3389/fimmu.2023.1183465
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-neutrophil crosstalk promotes in vitro and in vivo glioblastoma progression

Dominique S. Rubenich,
Priscila O. de Souza,
Natalia Omizzollo
et al.

Abstract: IntroductionThe tumor microenvironment (TME) of glioblastoma (GB) is characterized by an increased infiltration of immunosuppressive cells that attenuate the antitumor immune response. The participation of neutrophils in tumor progression is still controversial and a dual role in the TME has been proposed. In this study, we show that neutrophils are reprogrammed by the tumor to ultimately promote GB progression.MethodsUsing in vitro and in vivo assays, we demonstrate the existence of bidirectional GB and neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…Several SASP components, including IL-1β, IL-6, IL-8, and TNFα, are all potential targets for pharmacological inhibition; some of them already exist in the clinical practice and may be exploited to mitigate the deleterious effects of SASP in the relevant clinical context [22]. Interestingly, these cytokines are the key inflammatory mediators that trigger the inflammatory cycle in GBM and also promote carcinogenesis by avoiding growth suppression and apoptosis, inducing angiogenesis and metastasis, and maintaining cancer cell stemness [2,[23][24][25]. The concentration of cytokines in GBM cyst fluid highly correlates with white blood cell counts, suggesting an important interaction between tumor cells and the peripheral inflammatory status [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several SASP components, including IL-1β, IL-6, IL-8, and TNFα, are all potential targets for pharmacological inhibition; some of them already exist in the clinical practice and may be exploited to mitigate the deleterious effects of SASP in the relevant clinical context [22]. Interestingly, these cytokines are the key inflammatory mediators that trigger the inflammatory cycle in GBM and also promote carcinogenesis by avoiding growth suppression and apoptosis, inducing angiogenesis and metastasis, and maintaining cancer cell stemness [2,[23][24][25]. The concentration of cytokines in GBM cyst fluid highly correlates with white blood cell counts, suggesting an important interaction between tumor cells and the peripheral inflammatory status [24].…”
Section: Introductionmentioning
confidence: 99%
“…Second, neutrophils can also affect tumor immune escape and drug resistance by regulating the expression of cytokines and chemical factors in the tumor microenvironment ( 57 ). In addition, some studies have found that the number and activity of central granulocytes are closely related to the prognosis of tumors, and the high density of central granulocyte infiltration is related to the malignant degree and poor prognosis of tumors ( 58 ). In contrast, lymphocytes are the primary immune cell type and play a crucial role in eliminating tumor cells through immune surveillance ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils can inactivate T cells by secreting various cytokines, resulting in tumor immune evasion and progression 18 20 . Moreover, tumor-infiltrated neutrophils can promote tumor angiogenesis 21 , and tumor-neutrophil crosstalk sustains prolonged tumor activation 22 . Hence, various blood-based immunity-related biomarkers, including the neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), and systemic immune-inflammation index (SII), have been reported to be independent prognostic factors in cancer patients 23 25 .…”
Section: Discussionmentioning
confidence: 99%